The Relationship Between Intercourse Preference Positions and Personality Traits Among Gay Men in China. - Zheng, Lijun; Hart, Trevor; Zheng, Yong (Archives of Sexual Behavior, 2012)
Distinctions are commonly made regarding preferences for insertive or receptive anal intercourse within the gay male community. Three sexual self-labels are typically specified: 'top,' meaning a man who prefers the insertive position, 'bottom,' meaning a man who prefers the receptive position, and 'versatile,' meaning a man willing to perform either position. The aim of this study was to examine personality differences among these three groups in gay men in China. We sampled 220 Internet-obtained Chinese gay men on instrumentality, expressiveness, gender-related interests, self-ascribed masculinity- femininity (Self-MF), and Big Five personality traits. Significant differences were found among sexual self-label groups in sexual behavior and in gendered traits and interests. Tops scored higher than the bottoms on instrumentality, gender-related interests, and self-ascribed masculinity-femininity (Self-MF) and bottoms scored higher than tops on expressiveness. Versatiles' scores in gender-related traits were intermediate between that of tops and bottoms. There were no significant differences in Big Five traits among the three groups. Sexual self-labels appear not only to distinguish sexual behavior patterns but may also suggest gender role differences among Chinese gay men.